Root Canal Treatment of a Hypertaurodont Mandibular Second Molar: A Case Report - Davood Jamshidi; Alireza Adl; Fereshte Sobhnamayan; Mehrdad Bolurian (Tabriz University of Medical Sciences, 2015)
Taurodontism is a morphologic feature of generally multi-rooted teeth with large pulp chambers and shortened roots. A case of endodontic treatment in a 24-year-old male with the chief complaint of swelling and pain in the right mandibular region is described. Periapical lesion was present in the radiographic examination of hypertaurodont second mandibular molar.Four root canals were detected with an endodontic microscope. The canals were prepared and obturated with lateral conden-sation technique in the second appointment. The patient was asymptomatic in the 18-month follow-up.